PERSEPSI AUDITOR MENGENAI PENGARUH INDEPENDENSI DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Wahab, Hafidh Alifi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to assess and to analyze auditor’s perception on the effect of auditor independence and auditor ethics on audit quality with good corporate governance as a moderating variable. Data collection method used is survey method by distributing questionnaire. Respondents of this study are auditors who work on Public Accounting Firm in Malang and Surabaya, East Java. This study uses primary data by distributing 146 questionnaires to 22 Public Accounting Firms in Malang and Surabaya, East Java, which are registered with the Indonesian Institute of Certified Public Accountants. The sampling method used is purposive sampling and hypothesis testing is done with Statistical Product and Service Solutions (SPSS) software. The results of this research prove that ethics has an effect on audit quality. Meanwhile, independence, interaction between independence with good corporate governance, and interaction between ethics with good corporate governance have no effect on audit quality. The results also show that ethics is the most dominant factor in influencing an audit quality.Keywords : Independence, Ethics, Auditor, Good Corporate Governance, Audit Quality